Expanding outpatient benefits package can reduce diabetes-related avoidable hospitalizations - Liu, Hao-Ran; Chen, Si-Yuan; Zhang, Lan-Yue; Fu, Hong-Qiao; Jian, Wei-Yan (Frontiers in Public Health, 2023)
Objective To evaluate the policy effect of replacing hospitalization service with outpatient service and reducing diabetes-related avoidable hospitalizations by improving outpatient benefits package. Methods A database of hospital discharge from 2015 to 2017 in City Z was used. All diabetic inpatient cases enrolled in Urban Employee Basic Medical Insurance were selected as the intervention group, and diabetic inpatient cases enrolled in Urban and Rural Resident Basic Medical Insurance were selected as the control group. The Difference-in-Difference model was used to analyze the effect of improving outpatient benefits package level of diabetes from 1800 yuan (about 252.82) to 2400 yuan (about 337.09) per capita per year on avoidable hospitalization rate, average hospitalization cost and average length of stay. Results The avoidable hospitalization rate of diabetes mellitus decreased by 0.21 percentage points (P < 0.01), the average total cost of hospitalization increased by 7.89% (P < 0.01), and the average length of stay per hospitalization increased by 5.63% (P < 0.01). Conclusions Improving the outpatient benefits package of diabetes can play a role in replacing hospitalization service with outpatient service, reducing diabetes-related avoidable hospitalizations, and reducing the disease burden and financial burden.